Evaluation Of Anti Implantation And Abortificient Properties Of Portulaca Oleracea L. In Albino Rats - RAMESH LONDONKAR,; HANUMANTAPPA. B. NAYAKA, (International Journal of Pharma and Bio Sciences, 2011)
The present study was aimed to evaluate the effect of Portulaca oleracea L on fertility of female albino rats. Albino rats were orally administered with Petroleum Ether, chloroform and Ethanol crude extracts of aerial part of Portulaca oleracea L in both high and low dose (500mg and 250 mg / kg of body weight / day, for 7 days), and effect of crude extract on Anti implantation and Abortificient activity was investigated. The treatment of petroleum ether crude extract has shown 20% and 30% reduction in implantation activity at low (250) and (500) high doses respectively. In case of chloroform and Ethanol crude extracts, the chloroform extract has shown 50% and 60% reduction in implantation activity at low and high doses respectively, whereas Ethanolic crude extracts have shown 40% and 50% reduction in implantation sites with respect to low and high dose of extract treatment . Ethanolic crude extract treatment has shown abortificient activity but the petroleum ether and chloroform extract treatment to pregnant rats did not shown any abortificient activity.